2012
DOI: 10.4269/ajtmh.2012.11-0502
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable Risk Factors for West Nile Virus Infection during an Outbreak—Arizona, 2010

Abstract: Abstract. West Nile virus (WNV) is the leading cause of mosquito-borne disease in the United States; however, risk factors for infection are poorly defined. We performed a case-control study to identify modifiable risk factors for WNV infection. Case-patients (N = 49) had laboratory evidence of recent WNV infection, whereas control-subjects (N = 74) had negative WNV serology. We interviewed participants, surveyed households, and assessed environmental data. WNV infection was associated with living in or near W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
1
17
2
Order By: Relevance
“…This finding contradicts studies in Arizona which indicated that those who did not attend school were more at risk of the disease than those who attended school 11 . This is not surprising as literacy is generally a symbol of improved socioeconomic status leading to increased chances of access to medical care resulting in reduced chances of exposure to the disease 29 .…”
Section: Resultscontrasting
confidence: 88%
See 1 more Smart Citation
“…This finding contradicts studies in Arizona which indicated that those who did not attend school were more at risk of the disease than those who attended school 11 . This is not surprising as literacy is generally a symbol of improved socioeconomic status leading to increased chances of access to medical care resulting in reduced chances of exposure to the disease 29 .…”
Section: Resultscontrasting
confidence: 88%
“…Most of the infections are usually asymptomatic but those who show symptoms come down with headaches, myalgia, arthralgia and rash. Currently no treatment exists for arboviral diseases and there are no licensed vaccines for humans, therefore preventive measures against infection with WNV are encouraged [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…57 Others have documented the impact of human behavior and interventions on WNV incidence patterns such as mosquito control, neglected swimming pools that provide mosquito breeding habitat, or having water-holding containers in the backyard. [58][59][60] Similarly, the use of personal protection such as repellent is influenced by individual risk perception and may vary from year to year depending on media coverage and public health messaging. We have shown that using only annual temperature we can create a model that identifies higher than normal WNV disease incidence in a county with "fair" accuracy.…”
Section: 48mentioning
confidence: 99%
“…However, a case-control study conducted in the East Valley concurrently with our study identified three environmental or behavioral risk factors for WNV infection: the presence of water-holding containers around the residence, not working or attending school outside the home, and residence in an area served by irrigation. 2 This study also identified proximity to a neglected swimming pool as a risk factor by univariate analysis, but not by multivariate analysis. Neglected pools can serve as larval habitats capable of producing large numbers of both Cx.…”
Section: Discussionmentioning
confidence: 97%
“…On July 21, the Maricopa County Department of Public Health and the Arizona Department of Health Services requested assistance from the Centers for Disease Control and Prevention (CDC) in the outbreak investigation. The CDC response consisted of two components, 1) an epidemiologic component to assist the Maricopa County Department of Public Health with case finding and follow-up, and to conduct a case-control study to identify modifiable risk factors for WNV infection; 2 and 2) an entomologic/ecologic component to conduct investigations in the outbreak focus, and in a demographically similar control area having little or no documented WNV activity, and also to collaborate with the epidemiologic team assessing casepatient and control-subject residences for environmental risk factors of infection. In this report, we present the results of the entomologic investigations, specifically a comparison of entomologic parameters within and outside the outbreak area.…”
Section: Introductionmentioning
confidence: 99%